Study of interaction between extracellular matrix proteins and receptors of CD133+ stem cells and CD133– differentiated glioma cells - V. E. Shevchenko; I. S. Bryukhovetskiy; E. A. Savchenko; N. E. Arnotskaya (Успехи молекулярной онкологии)
Background. Treatment of glioblastoma multiforme remains little effective due to the rapidly developing recurrence of the tumor, due to its high tumorigenic potential, resistance to chemoradiation therapy and increased dissemination of glioma stem cells (GSC). Molecular mechanisms of these cell interaction with extracellular matrix (ECM) are practically not studied. At present, it is also not clear the signaling of the ECM-receptor interaction (ECM-RI) differs for GSC and differentiated glioma cells (GDC).Objective: using high-resolution proteomic mass spectrometry to study the determinant expression of the ECM-receptor interaction signaling cascade in CD133+ GSC and CD133–    GDC.Results. 1990 proteins are identified, 18 of which are associated with the ECM-RI process. Positive regulation of 14 ECM-RI proteins was found in CD133+ GSC compared with CD133–    GDC, ten had more than 2 times increased expression. Increase in the CD133+ GSC level of 4 proteins activating the ECM-RI signaling cascade was noted.Conclusion. Important regularities are determined that could be used for the development of new approaches for detection of potential therapy targets of glioblastoma multiforme.